(untitled) (Global Journal of Management and Business Research, 2013)
Present research is a comparison between the various dimensions of the performance management among the loyal and disloyal employees. A sample of 162 bank employees was selected randomly on availability basis for this research from a universe of bank employees of private and nationalized banks situated at Punjab, Haryana and National Capital Region of New Delhi. Selected employees were tested for their loyalty. On the basis of higher and lower scores of loyalty, employees were divided into two groups, each having 57 subjects. First group was consisting of the subjects who scored on the loyalty scale from 87-117 and nominated as group of disloyals. Whereas, second group was consisting of employee who scored 120-150 and this group was categorized as loyals. After formation of loyal and disloyal groups, subjects of both the groups were tested for the role in performance management. Performance Management was tested with its four major dimensions, such as "Organizational Planning", "Decision Making", "Effective Execution", and "Result Producing Capability". The mean scores for organizational planning among loyal and disloyal groups were (22.3) and (10.6) respectively. There was significant difference between the mean score values of organizational planning between the loyal and disloyal employees. The mean score values for the capability of decision making were (21.7) and (9.5) respectively. There was significant difference in the mean scores of loyal and disloyal groups. When the mean scores of third dimension i.e. effective execution of performance management for loyal and disloyal employees group were compared, they were found (20.4) and (13.2). The mean scores of loyal and disloyal group for effective execution also differ significantly.